Empowering Indonesian Language Education through Canva: A Collaborative Project by Multiple Universities - Asrofi, Asrofi; Masodi, Masodi; Santoso, Citra Reksi; Agustin, Faikotul Wulan; Zahroni, Ardhian; Suciati, Suciati (CV. BImbingan Belajar Assyfa, 2024)
This community service program aims to enhance the quality of Indonesian language teaching through collaboration among lecturers from Universitas Merdeka Malang, STKIP PGRI Sumenep, Universitas PGRI Adibuana Surabaya, and PT. Briliant Knowledge University. The program focuses on utilizing Canva technology to develop innovative teaching media, addressing the growing need for digital learning innovations. The Design-Based Research (DBR) approach facilitates collaboration between lecturers and teachers to design, implement, and evaluate new teaching methods. Teaching materials include infographics, interactive presentations, and learning videos created using Canva. Data collection methods include participatory observation, in-depth interviews, and questionnaires. Thematic analysis identifies patterns and themes from teacher experiences. Findings reveal Canva's effectiveness in boosting student motivation and engagement, with teachers reporting improved graphic design skills, enabling them to create more compelling teaching materials. The program demonstrates that technology-based mentoring can significantly enhance junior high school teaching quality. It underscores the importance of collaboration between higher education institutions and schools, improving technical skills and increasing teacher confidence in technology use. The study offers a mentoring model adaptable to various educational contexts, serving as a reference for institutions aiming to elevate teaching quality through technology. This initiative aspires to inspire collaborative educational innovations attuned to contemporary demands.